Hall current, viscous and Joule heating effects on steady radiative 2-D magneto-power-law polymer dynamics from an exponentially stretching sheet with power-law slip velocity: A numerical study. (1st December 2020) - Shamshuddin, MD.; Khan, Sami Ullah; Anwar Bég, O.; Bég, Tasveer A.
Highlights: Mathematical model developed for a power-law fluid flow through stretching sheet. Features of Joule heating and viscous dissipation are included in the model. Utilizing Runge-Kutta Fehlberg Method with shooting solutions have been obtained. Rapidly convergent and accurate solutions are achieved with both RKFM and GDQ. Abstract: A mathematical model is developed for 2-D laminar, incompressible, electrically conducting non-Newtonian (Power-law) fluid boundary layer flow along an exponentially stretching sheet with power-law slip velocity conditions in the presence of Hall currents, transverse magnetic field and radiative flux. The secondary flow has been induced with appliance of Hall current. The distinguish features of Joule heating and viscous dissipation are included in the model since they are known to arise in thermal magnetic polymeric processing. Rosseland's diffusion model is employed for radiation heat transfer. The non-linear partial differential equations describing the flow (mass, primary momentum, secondary momentum and energy conservation) are transformed into non-linear ordinary differential equations by employing local similarity transformations. The non-dimensional nonlinear formulated set of equations is numerically evaluated with famous shooting algorithm by using MATLAB software. The validation of simulated numerical results has been completed with generalized differential quadrature (GDQ). Extensive visualization of primary and secondary velocities and temperature distributions for the effects of the emerging parameters is presented for both pseudo-plastic fluids ( n = 0.8 ) and dilatant fluids ( n = 1.2 ). The study is relevant to the manufacturing transport phenomena in electro-conductive polymers (ECPs).